Topological Models of Generation and Formation of Latex Particles in the Monomer-Water System - A. A. Hovhannisyan; G. K. Grigoryan; N. G. Grigoryan; A. G. Nadaryan (Novel Aspects on Chemistry and Biochemistry Vol. 8, 2023)
The main method for synthesizing latexes is polymerization in a heterogeneous monomer–water system. This method is called emulsion polymerization. The performance properties of latexes are determined by the parameters of the colloidal system and the polymer material. These parameters are determined by the nature of the monomer and the mechanism of formation of latex particles. This article discusses existing models for the generation of latex particles and the possibility of regulating the colloidal parameters of latex based on them. The purpose of this work is to search for ways to synthesize latexes with a narrow particle distribution based on a topological model of emulsifier-free polymerization of monomers of different natures in a static monomer-water system. The article presents electron microscopic photographs of polystyrene latexes without emulsifiers, obtained in the presence of methyl and cetyl alcohol in styrene. Electron microscopic photographs of methyl methacrylate and vinyl acetate latexes, which were obtained without any additives to the system, are also presented. Electron microscopic studies show that static mode of polymerization in a heterogeneous monomer-water system can be considered as one of the most promising methods for the synthesis of monodisperse latices.